Wildlife Health and Public Trust Responsibilities for Wildlife Resources (International Journal of Innovative Research in Engineering & Management, 2021)
The growing concern among wildlife  experts and the public regarding animal health and  illnesses is a major trend in wildlife management.  Simultaneously, the wildlife profession is reconsidering  the ramifications of managing wild populations as a  people's confidence, as well as the obligation that comes  with it to preserve the quality (i.e., health) and long-term  viability of wildlife. It's an excellent time to emphasise the  importance of wildlife health as well as to advocate for  comprehensive and consistent wildlife health integration in  wildlife management. Researchers look at how public trust  principles have been applied to animal population control  in the United States in this research. Humans feel that  wildlife health is vital to fulfilling public trust administration obligations with relation to wildlife since it  is trustees' principal responsibility to protect the well-being  of wildlife species (i.e., the core resources of the trust). Since both wildlife hazard - health perception about the  threats posed by wildlife diseases to humans and  household pets are rising issues, wildlife sickness and risk  communication in connection to wildlife health are vital to  wildlife trust management. We suggest that wildlife health  specialists are critical to maintaining the wildlife trust, and  that current conditions enable wildlife health care  professionals to contribute significantly to wildlife  management.
Keywords: Animal; Health; Population; Resources